2012
DOI: 10.2478/10004-1254-63-2012-2162
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mercury-Based Medical Devices Across Croatian Healthcare Facilities

Abstract: In 2009, we conducted a survey to assess the use of mercury-based thermometers and sphygmomanometers and their disposal in Croatian healthcare facilities. The questionnaire addressing the use of mercury-based medical devices, waste management, preferences between mercury-based and electronic devices, and the knowledge on mercury toxicity was fi lled by ward nurses affi liated with 40 (71.4 %) out of 56 contacted healthcare facilities. Only one of these facilities had given up the use of mercury-containing medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Similar studies 25,26 have quantitatively evaluated the knowledge and use of mercury but have not evaluated risk perception. Karam 38 considers risk perception to be not only the perception of the probability of an event occurring but also a set of direct and indirect experiences in various situations that the individual presents, which, together with the acquired knowledge, result in an interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar studies 25,26 have quantitatively evaluated the knowledge and use of mercury but have not evaluated risk perception. Karam 38 considers risk perception to be not only the perception of the probability of an event occurring but also a set of direct and indirect experiences in various situations that the individual presents, which, together with the acquired knowledge, result in an interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable percentage of health professionals are inclined to use thermometers and sphygmomanometers that contain mercury because they believe that they are more precise. A study by Janev Holcer et al 26 reported that nurses prefer mercury-containing thermometers because they are accurate and reliable, although they may be slower. According to the study by Halder et al, 25 they prefer mercury-containing thermometers to digital thermometers because of their availability, affordability, precision, and ease of use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations